NANDONG: TRADISI LISAN SIMEULUE - Sanusi Ismail; Bustami Abubakar; Hasbullah; Azhari Aiyub (The Department of Islamic History and Culture in cooperation with the Center for Research and Community Service, Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2020)
Simeulue, located in the Indian Ocean, has attracted a lot of people’s attention after the tsunami hit the region in 2004. The low number of casualties in Simeulue compared to other affected made the island a spotlight for further research. Some people argue that some forms of oral traditions exist among the people of Simeulue have played a role in saving many lives from the impact of the disaster. Nandong is a popular oral tradition in Simeulue. This oral tradition is important and considered as local wisdom because it contains norms and values inherited by the Simeulue community from generation to generation. This article aims to explore the substance and existence of this local wisdom in the Simeulue community. This study was conducted using qualitative methods. Our research data were collected during fieldwork through interviews, participant-observation and archival reviews. This research found that nandong is a distinctive oral tradition that is different from other oral traditions exist in Simeulue such as buai, nanga-nanga, tokok-tokok and nafi-nafi. This study argues that nandong is the most influential oral tradition among the Simeulue community. Unfortunately, the future existence of nandong in Simeulue is at risk of extinction since not many people, especially the young generation, in Simeulue today eager learn the rich and profound teachings contained in nandong.